Osteoarthritis - Pereira, D. (2017)
Osteoarthritis is nowadays one of the most frequent chronic diseases and, with the increase in life expectancy, both its prevalence and incidence is expected to rise. This condition is progressive and leads to functional decline and loss in quality of life, with important health care and society costs. A review of relevant and recent literature on osteoarthritis was performed in PubMed. The purpose of this study is to understand important aspects about osteoarthritis estimates, burden of disease, pathophysiology, risk factors, diagnosis and treatment.